Orthopedic metallic hardware in routine abdomino-pelvic CT scans: occurrence and clinical significance. - Baliyan, Vinit; Kordbacheh, Hamed; Davarpanah, Amir H.; Mozafarry, Amirhossein; Sahani, Dushyant V.; Kambadakone, Avinash (Abdominal Radiology, 2019)
Purpose: To study the occurrence of orthopedic metallic hardware in routine abdomen/pelvic computed tomography (CT) scans and their impact on image quality (IQ) and diagnostic evaluation. Material and methods: In this retrospective single institution study, we analyzed 3500 consecutive abdomen/pelvis CT scans for occurrence of orthopedic metallic hardware. In the cohort of patients with metallic hardware detected on CT scans, subjective and objective IQ analysis was performed to estimate diagnostic acceptability (DA, 4-point scale), subjective noise (SN, 3-point scale), presence of artifacts (PA, 4-point scale) and objective noise. The clinical significance of metallic hardware was determined by evaluating the impact of artifacts on radiological diagnosis according to the clinical indication and disease type. Results: Orthopedic metallic hardware was encountered in 4.97% of abdomino-pelvic CT scans (n = 174/3500), and artifacts related to the hardware in the region of clinical interest were identified in 82% (n = 144/174) of scans. The overall mean DA was 2.66 (n = 174), and it was severely limited (score < 2) in 32% of cases particularly affecting patients with bilateral hip implants (92.6%, n = 25/27). The artifacts due to hardware significantly limited diagnostic evaluation in 58.6% of cases (PA score ≥ 3), and the image noise was unacceptable in 71% of cases (SN score > 2) in the region of clinical interest. Conclusion: Orthopedic metallic hardware is encountered in nearly 5% of abdomino-pelvic CT scans and causes significant image degradation limiting diagnostic evaluation in the region of clinical interest.